A seismic tomography, gravity, and flexure study of the crust and upper mantle structure of the Hawaiian Ridge: 1 - MacGregor, BG; Dunn, RA; Watts, AB; Xu, C; Shillington, DJ (Wiley, 2023)
The Hawaiian Ridge has long been a focus site for studying lithospheric flexure due to intraplate volcano loading, but crucial load and flexure details remain unclear. We address this problem using wide-angle seismic refraction and reflection data acquired along a ∼535-km-long profile that intersects the ridge between the islands of Maui and Hawai'i and crosses 80–95 Myr-old lithosphere. A tomographic image constructed using travel time data of several seismic phases reveals broad flexure of Pacific oceanic crust extending up to ∼200–250 km either side of the Hawaiian Ridge, and vertically up to ∼6–7 km. The P-wave velocity structure, verified by gravity modeling, reveals that the west flank of Hawaii is comprised of extrusive lavas overlain by volcanoclastic sediments and a carbonate platform. In contrast, the Hāna Ridge, southeast of Maui, contains a high-velocity core consistent with mafic or ultramafic intrusive rocks. Magmatic underplating along the seismic line is not evident. Reflectors at the top and bottom of the pre-existing oceanic crust suggest a ∼4.5–6 km crustal thickness. Simple three-dimensional flexure modeling with an elastic plate thickness, Te, of 26.7 km shows that the depths to the reflectors beneath the western flank of Hawai'i can be explained by volcano loading in which Maui and the older islands in the ridge contribute ∼43% to the flexure and the island of Hawai'i ∼51%. Previous studies, however, revealed a higher Te beneath the eastern flank of Hawai'i suggesting that isostatic compensation may not yet be complete at the youngest end of the ridge.